Factors Affecting Personal Hearing Protector (PHP) Use Among Industrial Workers: Development and Validation of the Questionnaire - Nur Syafiqah Fauzan; Ezrin Hani Sukadarin; Mirta Widia; Muhammad Faizal Zainal Abidin (Jurnal Optimasi Sistem Industri, 2025)
Personal hearing protectors (PHPs) used by industrial workers have already been a preferred measure in various industrial sectors that have issues with excessive noise exposure. Although personal hearing protectors (PHPs) are widely provided across industrial workplaces, actual worker compliance with their consistent and correct use remains notably low. Therefore, this study aimed to develop a valid measure to evaluate factors affecting PHP use among industrial workers in Malaysia. A questionnaire was developed on the factors affecting PHP use among industrial workers in Malaysia. The questionnaire comprised several items and was created using a systematic, thorough process consisting of three stages: (i) formulating items, (ii) translating them back-to-back, and (iii) subjecting them to expert content assessment by six (6) panels of experts. The questionnaire constructs and items were evaluated for content validity and reliability. The content validity score for each item was considered satisfactory. The Cronbach’s alpha was 0.940, indicating high overall internal consistency. The domain coefficients were as follows: interpersonal influence, 0.899; perceived severity, 0.902; perceived benefit, 0.868; perceived barrier, 0.893; perceived self-efficacy, 0.879; cues to action, 0.815; and use of PHP, 0.840. The domain coefficients demonstrated good to high internal consistency, ranging from 0.815 (cues to action) to 0.902 (perceived severity). This study shows that the questionnaire on factors affecting PHP use among industrial workers is valid and well-structured. Therefore, this study provides a valid and reliable tool for assessing factors influencing PHP use, which can inform the planning of targeted noise management programs.